Landschaft, Nationalparks und Fremdenverkehr am ostpatagonischen Andenrand.: Bericht über eine Forschungsreise - Eriksen, Wolfgang (ERDKUNDE, 1967)
Between November 1965 and September 1966 the author investigated changes in the pioneer border along the Andean fringe of east Patagonia (Provinces of Neuquen, Rio Negro and Chubut) with special reference to the effects of an influx of tourists. The cultural-geographical studies of Ljungner (journeys 1932-4) in the core area around Lake Nahuel (the so-called Argentinian Switzerland) were thus continued. The three landscape zones of the Andean Fringe (High Cordillera, Pre-Cordillera and Patagonian Table-land) are characterised by specific relationships of morphology, climate and vegetation and the development of the economic and settlement structure is illustrated. This shows that tourism is concentrated especially in the three National Parks of Lanin, Nahuel Huapi and Los Alerces and that its effects are twofold. On the one hand it limits the colonisation of the Andean fringe by restrictions on agriculture and forest use and the slow growth of various older State colonies. On the other hand, exceptional developments in population, settlement, economy and transport are encouraged at specific points, especially around the town of San Carlos de Bariloche.